Patron-clients in rice production process: Case study of rice mill entrepreneurs with rice farmers in North Mopuya II Village, North Dumoga District, Bolaang Mongondow Regency, North Sulawesi Province - Massenga, Talitha Wenifrida (International research journal of management, IT and social sciences, 2022)
The presence of rice milling entrepreneurs in the lowland rice production process has a strong influence so that rice farmers depend on entrepreneurs and it is difficult to get out of the patron-client relationship that has been built by the two. Entrepreneurs are present as "saviors" of the farmers in the context of socio-economic problems where farmers lack capital in the process of producing lowland rice and to meet urgent daily needs. The purpose of this study is to describe the patron-client relationship that occurs in the production process of lowland rice farming using descriptive qualitative research methods. As a research strategy, a case study was used on rice milling entrepreneurs and lowland rice farmers in Mopuya Utara II Village, Dumoga Utara District, Bolaang Mongondow Regency, North Sulawesi Province. The results of this study indicated that the dependence of farmers on rice mill entrepreneurs was built through a long friendship process and a sense of reluctance in which the entrepreneurs were considered "saviors" because they provided social security to farmers even though in reality entrepreneurs got bigger profits.